IVIG ameliorate inflammation in collagen-induced arthritis: projection for IVIG therapy in rheumatoid arthritis. (26th October 2020) - Halpert, G; Katz, I; Shovman, O; Tarasov, S; Ganina, K K; Petrova, N; Tocut, M; Volkov, A; Barshack, I; Blank, M; Amital, H
Summary: Rheumatoid arthritis (RA) is a systemic inflammatory autoimmune disease that leads to joint destruction and disability. Despite a significant progress in administration of biological agents for RA patients, there is still a need for improved therapy. Intravenous immunoglobulins (IVIG), a pooled polyspecific immunoglobulin (Ig)G extracted from 5000 to 20 000 healthy subjects, showed beneficial therapeutic effect in patients with immune deficiency, sepsis and autoimmune diseases. The current study aimed to investigate the beneficial effect of treatment with IVIG in established collagen-induced arthritis in DBA/1j mice. Murine arthritis was induced in DBA/1j mice. Treatment with IVIG began when the disease was established. The clinical score was followed twice a week until day 48. The mice were bled for plasma and the paws were hematoxylin and eosin (H&E)-stained. Cytokine profile in the plasma was analyzed by Luminex technology and titers of circulating anti-collagen antibodies in the plasma was tested by enzyme-linked immunosorbent assay. Our results show that treatment with IVIG in murine significantly reduced the clinical arthritis score ( P < 0·001). Moreover, mode of action showed that IVIG significantly reduced circulating levels of inflammatory cytokines [interferon (IFN)-γ, interleukin (IL)-1β, IL-17, IL-6, tumor necrosis factor (TNF)-α, P < 0·001], inhibiting anti-collagen antibodies ( P < 0·001) in the plasma of collagen-induced arthritis mice. Importantly, histopathological examination revealed that IVIG treatment prevented the migration of inflammatory immune cells into the cartilage and synovium, reduced the extent of joint damage and preserved joint architecture. Our results proved for the first time the valuable anti-inflammatory treatment of IVIG in experimental RA. We propose IVIG therapy for a subgroup of patients with rheumatologically related diseases. Graphical Abstract: